2022
DOI: 10.7759/cureus.25943
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Compliance Issues to Anti-glaucoma Medications Before and After a Structured Interventional Program

Abstract: BackgroundGlaucoma is one of the most common eye diseases in the elderly and the major cause of irreversible vision loss worldwide. Adherence to life-long therapies is crucial to prevent glaucoma progression. The current study aims to assess the educational element and its impact on glaucoma medication compliance over short and long periods. MethodsThis was a survey-based, prospective, interventional study, conducted via interviews of all glaucoma patients presented to the Ophthalmology Center at King Abdullah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
0
0
Order By: Relevance
“…All the included studies [1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were conducted between the years 2011 and 2022, with most of them in the few recent years. Most studies were conducted in Riyadh (n=11), followed by Jeddah (n=4).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…All the included studies [1,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were conducted between the years 2011 and 2022, with most of them in the few recent years. Most studies were conducted in Riyadh (n=11), followed by Jeddah (n=4).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The authors found that nearly half of the participants thought the patients could not be aware of their glaucoma from the symptoms. In comparison, Subhan et al [26] explored the effects of a structured interventional program on the compliance of glaucoma patients to anti-glaucoma medications. The authors noticed a significant improvement in the patient's compliance from 84.3% to 92.5%.…”
Section: Riyadh Glaucoma Patientsmentioning
confidence: 99%